Vagus nerve stimulation for the treatment of heart failure: the INOVATE-HF trial - Gold, Michael R.; Borggrefe, Martin (Journal of the American College of Cardiology, 2016)
Background - Heart failure (HF) is increasing in prevalence and is a major cause of morbidity and mortality despite advances in medical and device therapy. Autonomic imbalance, with excess sympathetic activation and decreased vagal tone, is an integral component of the pathophysiology of HF. - Objectives - The INOVATE-HF (Increase of Vagal Tone in Heart Failure) trial assessed the safety and efficacy of vagal nerve stimulation (VNS) among patients with HF and a reduced ejection fraction. - Methods - INOVATE-HF was a multinational, randomized trial involving 85 centers including patients with chronic HF, New York Heart Association functional class III symptoms and ejection fraction ≤40%. Patients were assigned to device implantation to provide VNS (active) or continued medical therapy (control) in a 3:2 ratio. The primary efficacy endpoint was composite of death from any cause or first event for worsening HF. - Results - Patients (n = 707) were randomized and followed up for a mean of 16 months. The primary efficacy outcome occurred in 132 of 436 patients in the VNS group, compared to 70 of 271 in the control group (30.3% vs. 25.8%; hazard ratio: 1.14; 95% confidence interval: 0.86 to 1.53; p = 0.37). During the trial, the estimated annual mortality rates were 9.3% and 7.1%, respectively (p = 0.19). Quality of life, New York Heart Association functional class, and 6-min walking distance were favorably affected by VNS (p < 0.05), but left ventricular end-systolic volume index was not different (p = 0.49). - Conclusions - VNS does not reduce the rate of death or HF events in chronic HF patients.